PEMBERDAYAAN MASYARAKAT BERBASIS POTENSI LOKAL DALAM PROGRAM “MERINTIS KAMPUNG LITERASI MEDIA DI DESA WARUNGASEM KECAMATAN WARUNGASEM KABUPATEN BATANG, JAWA TENGAH” - Ahmad Hidayatullah; Muhandis Azzuhri; Teddy Dyatmika (Lembaga Penelitian dan Pengabdian kepada Masyarakat (LPPM) - Universitas Muhammadiyah Cirebon, 2019)
Technological progress is a necessity that must be faced by all parties, including the emergence of positive and negative impacts that exist. Furthermore, this inability to cope with change and progress will bring about the consequences of negative impacts, including those related to media development. And this must be overcome, through various efforts, one of which is the media literacy movement. Using qualitative research methods that are done by working with data, organizing data, sorting it out, searching and finding patterns, finding what is important to report, this article tries to uncover how the implementation of Local Potential-based Community Empowerment in the